PENGARUH GOOD CORPORATE GOVERNANCE, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL PERFORMANCE DENGAN SUSTAINABILITY REPORT SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Manufaktur yang Go Public yang Terdaftar di BEI Periode 2013-2015) - Saputra, Ardiyansyah Eka; Halim, Edyanus Herman; Haryetti, Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of Good Corporate Governance (GCG), profitability (ROE) and Company Size (SIZE) of the Financial Performance by the Sustainability Report as an intervening variable. Endogenous variable in this study is the Sustainability Report and Financial Performance, while variable eksogenous is Good Corporate Governance, Profitability and Company Size. The population in this research is manufacturing companies listed in Indonesia Stock Exchange (IDX) in the period from 2013 to 2015 as many as 137 companies. By using purposive sampling technique samples that meet the criteria of 75 companies. Data processing using path analysis. The results showed that the variables of good corporate governance and significant positive effect on the sustainability report and the profitability of positive and significant impact on financial performance. Meanwhile, profitability and significant negative effect on the variable sustainability report. For further research using more accurate data with the amount of data more and with a longer time span. Besides analyzing the variables sustainability report on all aspects: social, economic, and environmental. In addition, by using the method and test equipment more complete and accurate so as to obtain a more valid conclusions.Keywords : Good Corporate Governance, profitability, firm size, Sustainability Report, and Financial Performance